MARTHA NUSSBAUM E A FUNÇÃO DAS EMOÇÕES NA CONSTITUIÇÃO DE UMA EDUCAÇÃO PARA A DEMOCRACIA - DUDA, BIANCA CARRARO (2023)
This investigation, of basic nature, is guided by a hermeneutic phenomenological analysis, using the technical procedures of bibliographical research. It seeks to answer the following question: What is the function of the education of emotions for the effectiveness of education for democracy? To answer it, the theory of emotions by philosopher Martha Nussbaum (2004, 2006, 2008, 2014, 2015, 2019) is the starting point. This perspective points out the cognitive character of emotions and argues about the importance of cultivating certain emotions for democratic stability and, consequently, for the constitution of education for democracy. Thus, the general objective of this research is to explain the importance of the education of emotions, based on Nussbaum's theorizations, for the realization of education for democracy. To achieve this goal, three specific objectives were established, which guided the organization of the three chapters of the dissertation: the first chapter aims to present the concept of emotion and the features that makeup Nussbaum's cognitive-evaluative theory; the second chapter aims to explain how the theory of emotions makes it possible to talk about their education, highlighting the emotions of primitive shame and projective disgust that, according to the philosopher, can be harmful to democracy; the third chapter, among other things, inserts Nussbaum's thought in the political field, explaining what kind of democracy is advocated by the author and presenting the three skills that, from her point of view, are essential for democratic citizenship. It also emphasizes some pedagogical strategies that can stimulate emotions allied to democracy, especially compassion, and, by addressing them, it argues that arts and literature have a central role in the education of emotions. As a final consideration, we intend to argue that Nussbaum's theory of emotions can contribute to the debate about the ways to implement education for democratic citizenship.